Influence of the Net Promoter Score of Retailers on the Willingness of Consumers to Install Their Mobile App - Wohllebe, Atilla; Ross, Florian; Podruzsik, Szilárd (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Mobile apps have become massively more important in the retail sector in recent years. A central challenge for retailers is the acquisition of new users for their mobile apps. A potentially interesting target group for this can be a company's existing, satisfied customer base, whereby customer satisfaction is often measured by the willingness to recommend the app or the Net Promoter Score. This paper investigates the influence of the willingness to recommend a retailer by consumers on their willingness to install a mobile app from this retailer. The influence of usage habits is also examined. The analysis of a survey of 105 consumers on a total of five retailers can confirm the hypotheses regarding the willingness to recommend a retailer and the Net Promoter Score (NPS) in particular: With the willingness to recommend, the willingness to install a retailer's app also increases.